2017
DOI: 10.1037/pag0000185
|View full text |Cite
|
Sign up to set email alerts
|

The role of stimulus complexity and salience in memory for face–name associations in healthy adults: Friend or foe?

Abstract: The Associative Deficit Hypothesis (ADH) posits that age-related differences in recognition of associations are disproportionately larger than age differences in item recognition because of age-related difficulty in binding and retrieval of two or more pieces of information in a memory episode. This proposition rests on the observation of disproportionately greater age differences in memory for associations than in recognition of individual items. Although ADH has been supported in experiments with verbal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
5
1
Order By: Relevance
“…Relatedly, Hertzog, Kidder, Powell-Moman, and Dunlosky [44] found aging did not affect metacognitive monitoring during encoding, despite a decline in associative memory. These results challenge the suggestion that impairment in metamemory explains the associative deficit in older adults [42, 43].…”
Section: Introductioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Relatedly, Hertzog, Kidder, Powell-Moman, and Dunlosky [44] found aging did not affect metacognitive monitoring during encoding, despite a decline in associative memory. These results challenge the suggestion that impairment in metamemory explains the associative deficit in older adults [42, 43].…”
Section: Introductioncontrasting
confidence: 77%
“…Some researchers have posited metamemory (i.e., metacognition in the memory domain) as a predictor of the age-specific associative memory deficit (e.g., [42, 43]) but few have actually asked participants to report metacognitive judgments during tests of the age-related associative deficit. In one study, self-reported metamemory beliefs were significantly related to strategy success and associative memory [14].…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis by Old and Naveh-Benjamin (2008) showed that the effect of age was more pronounced under intentional instructions. However, a recent study indicates that at least part of the effect might not be explained by encoding instructions, but by differences in salience and complexity of stimuli used in different experiments (Bender, Naveh-Benjamin, Amann, & Raz, 2017). Bender et al (2017) showed that older adults only showed a disproportionate deficit for face-name associations when the face stimuli were more complex, but not when standardized grayscale faces without visual context were used.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, increasing environmental support can improve memory (Craik et al, 1986). More specifically, Bender et al (2017) recently showed that, regardless of the observer’s age, highly distinctive, colored face stimuli and accompanied by multiple non-facial details, as well as salient characteristics such as eye color and head rotation, are easier to recognize and require shorter processing time than less distinctive, grayscale face stimuli. Thus, enriching stimuli by adding external contextual cues – namely, keeping the colored version of the portraits and attributing names to the individuals – may be a plausible way to enhance their ecological validity and therefore increase their salience for older adults.…”
Section: Introductionmentioning
confidence: 99%